2002
DOI: 10.1007/s00424-002-0793-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of cell surface β-adrenoceptors in different rat skeletal muscles

Abstract: In the present study, the density of cell surface beta-adrenergic receptors was determined in different skeletal muscles using the hydrophilic ligand [3H]CGP 12177. The density of beta-adrenergic receptors was highest in the slow-twitch soleus muscle (32.8+/-0.9 fmol mg dw(-1)) and lowest in the fast-twitch glycolytic white gastrocnemius (10.4+/-0.5 fmol mg dw(-1)) beta-Adrenoceptor density correlated closely with the percentage of type-I fibres (r=0.979; P<0.0001) and inversely with the percentage of type-IIB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 39 publications
3
35
1
2
Order By: Relevance
“…The present results suggest that the different effects of clenbuterol on β 2 -AR mRNA expression between fasttwitch fiber-rich EDL and slow-twitch fiber-rich SOL muscles are associated with the intracellular factors without any association with the number and distribution of β 2 -AR molecules. In contrast, it was reported that the decrease of β-AR densities on the cell surface was dependent on the receptor density in each muscle fiber, although the details are unclear (27).…”
Section: Effects Of Clenbuterol On β 2 -Ar Mrna Expression In Skeletamentioning
confidence: 93%
See 1 more Smart Citation
“…The present results suggest that the different effects of clenbuterol on β 2 -AR mRNA expression between fasttwitch fiber-rich EDL and slow-twitch fiber-rich SOL muscles are associated with the intracellular factors without any association with the number and distribution of β 2 -AR molecules. In contrast, it was reported that the decrease of β-AR densities on the cell surface was dependent on the receptor density in each muscle fiber, although the details are unclear (27).…”
Section: Effects Of Clenbuterol On β 2 -Ar Mrna Expression In Skeletamentioning
confidence: 93%
“…These muscle fibers are different in the velocity of contraction, metabolic properties, and β-AR distributions (4,7,14,15,25). Jensen et al (26,27) reported that the β 2 -AR subtype was contained in about 80% -95% of total β-ARs in skeletal muscles and relatively higher in the slow-twitch fiber-rich SOL muscle than in the fast-twitch fiber-rich EDL muscle. The effects of β-adrenergic stimulations on β 1 -and β 2 -AR mRNA expressions in muscle fibers, however, are still not elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…47 De fato, o primeiro estudo de internalização de receptor β2-adrenérgico demonstrou que após 30 minutos de estimulação por agonista β2-adrenérgico, cerca de 50% dos receptores do mús-culo sóleo foram internalizados e somente 30% retornaram a superfície celular. 48 Portanto, cronicamente a hiperatividade simpática levaria à internalização dos receptores β-adrenérgicos, o que levaria à degradação protéica da musculatura esquelética.…”
Section: Figura 4: Principais Causas Das Lesões Causadas Ao Organismounclassified
“…It is estimated that 80% -95% of the skeletal muscle β-adrenoceptors are of the β 2 -subtype, but β 1 -adrenoceptors have also been detected (2,3). Furthermore, Hirata et al (4) observed the reduction in β-adrenoceptors and the occurrence of α-adrenoceptors in the rat soleus muscle, predominantly during hypokalemia.…”
mentioning
confidence: 99%